NATURALISM AND ITS RELEVANCE IN THE CONTEMPORARY SYSTEM OF EDUCATION - Rafiyah Rasool (PT. Radja Intercontinental Publishing, 2023)
Naturalism in education emphasizes learning through experience and exploration rather than relying solely on textbooks and lectures. It aligns with the idea that education should reflect real-life scenarios and encourage students to develop critical thinking, problem-solving, and social skills in practical contexts. In the present system of education, naturalism remains relevant as it promotes a holistic approach to learning that complements traditional academic methods. Incorporating naturalistic principles into education encourages students to connect classroom learning with their everyday lives, fostering deeper understanding and application of knowledge. This approach also supports personalized learning experiences, catering to individual interests and learning styles, thereby enhancing engagement and motivation among students. Moreover, naturalism in education promotes environmental awareness and sustainability by encouraging direct interaction with nature and ecological systems. Despite its benefits, implementing naturalism requires balancing structured curricula with flexible, experiential learning opportunities. Educators must integrate hands-on activities, field trips, and project-based learning effectively to maximize its impact. By embracing naturalistic principles, the modern education system can better prepare students for the complexities of the 21st century, equipping them with both academic knowledge and practical skills essential for future success.